Fault Detection of Bearing using Support Vector Machine-SVM - Borhana A.A.; Bin Mustaffa Kamal D.D.; Latif S.D.; Ali Y.H.; Ahmed Almahfoodh A.N.; El-Shafie A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bearings (machine parts); Fault detection; Bearing failures; Input variables; Reliable models; Rolling elements; Support vector machine models; Trial-and-error method; Vibration frequency; Vibration signal; Support vector machines